Development of motivation and functional preparation for competitions at the rugby players in the Children's Sports School (Journal of Pedagogical Inventions and Practices, 2023)
The article discusses issues on the development of rugby in Uzbekistan, the presidential decree on the development of rugby in our country, rugby as a symbiosis of athletics and freestyle wrestling, motivation among rugby players in the Sports and Youth Sports School and their physical, moral, mental and tactical training. Running as a vital element for rugby players. Ball throwing. Motivate rugby players because rugby is a team game, so every detail of each player is important here, taking into account the understanding of rugby players among themselves during training and in competitions Motivation as a complex solution to the problems of team sports